Pembuatan Kitosan dari Cangkang Udang sebagai Adsorben Emas (Au) - Indra Jaya; Joni Syaputra; Dwi Sabda Budi Prasetya; Dwi Pangga (Lensa: Jurnal Kependidikan Fisika, 2017)
[Title: Making Chitosan From Shrimp Cup As Gold (Au) Adsorben]. This study aims to make chitosan from shrimp shell as golden adsorbent. Stages of chitosan preparation include demineralization stage using 1,5M HCL, deproteination stage using 3.5% NaOH to obtain chitin powder, then followed by chitin deacetylation stage using 60% NaOH to produce an anime that is chitosan. Subsequently, the chitosan obtained was characterized, analyzed functional group with FTIR and determined its adsorption capacity against Au metal ion, Au content in the sample before and after adsorption was measured using AAS. The results showed chitosan characterization as follows: rendeman 45.83%, have powder texture, white colour, odourless, have moisture content 1.55%, perfectly soluble in glacial acetic acid 2% and purple positive with ninhydrin solution showed chitin has turned into chitosan. Based on calculations from the results of the resulting chitosan FTIR data has a degree of deacetylation 71.17%. From the result of analysis by using AAS that chitosan obtained able to adsorb Au metal from concentration 8.55 ppm decrease until 5,09 ppm with adsorption percentage equal to 40.46%.